PENGGUNAAN THIDIAZURON, 2, 4 – D DAN GIBERELLIN DALAM PEMBENTUKAN EMBRIO SOMATIK PULE PANDAK (Rauvolfia serpentina (L.) Benth. ex Kurz) MELALUI KULTUR in vitro - Heru Sugito; Yanto Santosa; Edhi Sandra (Department of Forest Resources Conservation and Ecotourism - IPB University, 2006)
Rauvolfia serpentina (L.) Benth. ex Kurz, is one of the tropical forest plant species which is exploited as plant medicine and pertained as world rareness. To be able to make balance to storey, level request of Rauvolfia serpentina (L.) Benth. ex Kurz simplisia raw material and saving it from destruction, require to be by activity of conservation, one of the effort by in vitro culture forming of somatic embryo. Somatic embryo by in vitro is forming of embryo from cell is non sexual which is culture. Somatic embryo application beside for the of quickly, also can be yielded by the amount of seed which is not limited its amount, as well as to support program repair of crop. This research to know giving influence and regulator dose grow, consist of 2 attempt. I. Factorial Attempt which use completely randomized experimental disign, what consist of 2 factor, first is thidiazuron concentration which consist of 4 level, that is 0 ppm 2 ppm, 4 ppm, 6 ppm, 8 ppm, second is concentration 2, 4-D which consist of 4 level, that is 0 ppm, 0.5 ppm, 1 ppm, 1.5 ppm, 2 ppm .II. Factorial Attempt which use completely randomized experimental disign, what consist of 2 factor, first is thidiazuron concentration which consist of 4 level, that is 0 ppm, 2 ppm, 4 ppm, 6 ppm, 8 ppm, second is giberellin concentration which consist of 4 level, that is 0 ppm, 0.5 ppm, 1 ppm, 1.5 ppm, 2.0 ppm. Pursuant to manner statistical analysis result is non parametric Kruskal-Wallis to callus score and embryo at 14 day after initiation not there are difference between treatment, but 28 and 42 day after initiation there are difference between treatment. The use thidiatzuron + 2,4-D give, forming of somatic embryo with the best treatment (6 ppm Thidiatzuron + 0,5 ppm 2, 4 D). Growth of embryo happened at age 35 day after initiation. Thidiazuron + giberellin forming of callus only.Key word : Rauvolfia serpentina, thidiazuron, 2,4-D, giberellin, somatic embryo